Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Sesudah Berlakunya Peraturan Pemerintah Nomor 46 Tahun 2013(Studi Kasus pada Wajib Pajak yang Terdaftar di KPP Pratama Surakarta) - Rahmanda, Adhitya Wahyu; , Drs. M. Abdul Aris , M.Si (2015)
This study aims to analyze the influence of awareness of tax payment, knowledge and understanding of tax regulation, the quality of service, and ease to taxpayer compliance after validity of Government Regulation Number 46 Year 2013. The population of this study are taxpayer who registered in KPP Pratama Surakarta. The sample of this study is taken with Slovin formula. There are 78 questionnaires that can be processed. The method to gathering the primer data is used survey method with questionnaire media. The analyze of data used in this study is multiple linear regression test with SPSS 17.0 program. Based on the result of research on this study is awareness of tax payment, the quality of service, and ease influence taxpayer compliance. While knowledge and understanding of tax regulation doesn't influence taxpayer compliance